Biofunctional Beverage: Antihyperglycemic Effect of Green Tea in Alloxan Induced Diabetic Rabbits - Zakir, Muhammad; Sultan, Khushbakht; Munir, Yusra; Ahmad, Sohail; Amin, Surriya; Khan, Murad A.; Khan, Haroon (Current Bioactive Compounds, 2019)
Background: Diabetes is a chronic metabolic syndrome that affecting millions of people around the world. There are several therapeutic options for the treatment of diabetes but adequate glycemic control is still a challenge. In this regard, daily food item has been focus to evaluate their effect on blood glucose control. Methods: Our study investigated the effect of oral consumption of crude extract and its subsequent solvent fractions (hexane, ethyl acetate and aqueous) of Green Tea purchased from local market in alloxan- induced diabetic rabbits. Plasma glucose level and overall affect on body weight was observed on daily basis up t 26th day at 25 and 50 mg/kg p.o. Results: The results showed significant (P<0.05) reduction in hyperglycemia-induced in rabbits. The crude extract was most dominant in its effect after 26th of administration, while hexane fraction did not produce any antihyperglycemic effect. However, the remaining fractions elicited moderate effects. When the effect of these extracts were studied on body weight of diabetic rabbits, marked recovery in body weight was observed. Conclusion: In short, it is concluded, that the various extracts of green tea possessed strong antidiabetic and weight regaining effects in alloxan-induced diabetic rabbits, and thus appeared as a significant biofunctional food in diabetes management. Furthermore, bioactivity guided isolation of secondary metabolites could provide chemical background.
Keywords: Green tea